Islamic Religious Education and Global Issues: Developments in Science and Artificial Intelligence (AI) - Yuyun Ningsih; Muhammad Zuhdi; Bobi Erno Rusadi (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Islamic Religious Education (PAI) addresses global issues related to the development of science and artificial intelligence (AI). PAI encourages the pursuit of knowledge as part of worship, as taught in the Qur'an, and can align science with Islamic values to understand Allah SWT's creation. The development of AI raises ethical issues, such as privacy, discrimination, unemployment, and security risks, while also opening opportunities for halal innovation. From the perspective of PAI, AI must be used in accordance with the maqasid sharia for the common good, avoiding misuse that contradicts the principles of honesty and justice. Recommendations include updating the PAI curriculum to improve AI literacy. In conclusion, PAI can serve as a guide for the responsible use of AI, making it a tool for harmony between religion, science, and technology.